Faktor yang Mempengaruhi Pengambilan Keputusan dalam Menitipkan Anak di Taman Penitipan Anak (TPA) - Dessy Putri Wahyuningtyas (Insititut Agama Islam Negeri (IAIN) Curup, 2022)
Daycare is an alternative care service for working parents. The occurrence of a paradigm shift where currently many mothers work has implications for the role of care that is taken over by social institutions. So this study aims to explore what factors influence mothers' decision-making in leaving their children at Balita Ceria Daycare. This research uses a qualitative method with a phenomenological approach. The subjects in this study used a purposive sampling technique with the criteria of working mothers, choosing the Fullday program, and having children aged 0 - 5 years or not yet attending kindergarten. The results of the research on factors influencing decision-making in leaving children there are five factors originating from parents, namely work opportunities, professionalism, time management, lower stress and fatigue levels due to work, and independence in households. Other factors related to daycare are curriculum and learning, legality, distance, communication, and safety and comfort of TPA for child development.